Lattice-mismatch-free growth of organic heterostructure nanowires from cocrystals to alloys - Qiang Lv; Xue-Dong Wang; Yue Yu; Ming-Peng Zhuo; Min Zheng; Liang-Sheng Liao (Nature Communications, 2022)
The large-scale synthesis of organic heterostructure nanowires is challenging. Here, the authors report the synthesis of organic triblock nanowires via a lattice mismatch-free strategy.